A BRIEF HISTORY OF ENGLISH SATIRE - Мухиддинова (Абдуллаева) Дилафруз Мансуровна (Galaxy International Interdisciplinary Research Journal, 2023)
This article focuses on the Satire in English literature which has been an integral part of any period since the Middle periods, when the first sarcastic essays were published, as well as fables. The Renaissance in England was less significant in terms of the development of Satire. The theme of snobbery and the domination of plutocrat are the leading motifs of sarcastic stories and novels by William Thackeray. “A snot is one who looks with disgusting arrogance at all who are below him, and with vile admiration at all who are over, ” which provides excellent ground for the sarcastic depiction of similar characters.